2009
DOI: 10.1590/s0036-46652009000600003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of human t-cell lymphotropic virus type 1 (HTLV-1) Infection on laboratory parameters of patients with chronic hepatitis C virus

Abstract: SUMMARYHepatitis C virus (HCV) and human T-cell lymphotropic virus type 1 (HTLV-1) share routes of transmission and some individuals have dual infection. Although some studies point to a worse prognosis of hepatitis C virus in patients co-infected with HTLV-1, the interaction between these two infections is poorly understood. This study evaluated the influence of HTLV-1 infection on laboratory parameters in chronic HCV patients. Twelve HTLV-1/HCV-coinfected patients were compared to 23 patients infected only w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
4
19
0
Order By: Relevance
“…23 However, other groups have postulated that HTLV-1 infection can attenuate hepatic damage, as shown by lower serum levels of aminotransferases and lower degrees of liver fibrosis. 27,28 Similar results were observed in a study with triple HIV, HCV, and HTLV-1 co-infection, in which HTLV-1-infected patients presented better outcomes for HCVassociated liver fibrosis. 26 The present study was performed to provide new insights into the interactions between HCV and HTLV-1 infections through an evaluation of abnormalities in hepatic parameters and the neurological outcomes of HCV/HTLV-1 co-infection.…”
Section: Introductionsupporting
confidence: 76%
“…23 However, other groups have postulated that HTLV-1 infection can attenuate hepatic damage, as shown by lower serum levels of aminotransferases and lower degrees of liver fibrosis. 27,28 Similar results were observed in a study with triple HIV, HCV, and HTLV-1 co-infection, in which HTLV-1-infected patients presented better outcomes for HCVassociated liver fibrosis. 26 The present study was performed to provide new insights into the interactions between HCV and HTLV-1 infections through an evaluation of abnormalities in hepatic parameters and the neurological outcomes of HCV/HTLV-1 co-infection.…”
Section: Introductionsupporting
confidence: 76%
“…It has been well documented that HTLV induces polyclonal proliferation [Tygstrup, 1990]. Another study conducted in a Brazilian center found a similar result [Cardoso et al, 2009].…”
Section: Discussionmentioning
confidence: 64%
“…No particular risk factor could be identified for HTLV/HCV coinfected patients in Brazil. The use of intravenous drugs did not seem to be an important risk factor for these parenterally transmitted viruses; however, the use of unsafe injections for licit medicines in the past was likely responsible for most cases of HCV transmission in many parts of the country during the 1970s and 80s [Paraná et al, ; Cardoso et al, ; Milagres et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study showed that liver enzymes were higher in patients with hepatitis C virus (HCV)/HTLV1 coinfections than single HCV infections. 23 However, the difference observed has no clinical significance (4 units) and both medians are well below the upper limit of the normal range. During multivariate analysis, using a The main limitation of this study is its retrospective design, leading to numerous missing variables.…”
Section: 15mentioning
confidence: 84%